Salmonella enterica serovar Typhimurium-induced alterations in inflammatory chemokine mRNA expressions and hemato-biochemical variations in three different strains of chicken - Mir, Shabir; Ganai, Nazir A.; Ahmad, Syed M.; Hussain, Ishraq; Sheikh, Gowhar G.; Nabi, Nusrat; Rudayni, Hassan A.; Allam, Ahmed A. (Frontiers in Genetics, 2026)
This study aimed to understand the differential and tissue-specific immune responses of three different chicken strains [Vanraja, Kashmir Commercial Layer (KCL), and broiler] by assessing the CXCLi1 chemokine mRNA expression in different tissues (liver, spleen, and cecum) in Salmonella Typhimurium-challenged birds. In addition, hematological and biochemical parameters were also assessed. Salmonella enterica serovar Typhimurium culture was used for induction of infection. Differential expression of the CXCLi1 gene following induced infection was studied on different days post-infection (0, 1, 3, 5, 7, 9, 11, 13, and 15). An infection dose of 2 × 108 CFU/mL produced the symptoms characteristics of salmonellosis. An immune response gene expression study revealed enhanced expression until the 5th–7th day post-infection, followed by a steady decrease until the 15th day post-infection. The overall gene expression was higher in broiler chicks than in KCL and Vanraja chicks. The tissue-specific response showed higher expression in the cecum followed by the spleen and liver. The real-time mRNA gene expression results indicated that commercial broilers are more susceptible than backyard chicks. Differential cellular responses revealed heterophilia and initial lymphopenia followed by lymphocytosis. Pronounced hemato-biochemical alterations were observed as the clinical indicators of Salmonella infection. These findings imply that the integration of disease-resistant alleles from indigenous or backyard poultry into high-performance exotic germplasm could improve Salmonella resistance in commercial poultry populations.